(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Conclusions are drawn from this study by investigating models, frameworks, and policy impacts on health insurance systems in India. This research looks at the public health insurance programs of the US, India, South Korea, Australia, Finland, Kenya, and the UK. Emphasis is placed on AB-PMJAY. A variety of research methods are employed in this study. The coverage, financial security, system governance, health equity, efficiency, and sustainability of health insurance are evaluated in this study using quantitative and qualitative metrics. Rates of maternal and infant mortality, healthcare expenditure per capita, health insurance penetration, and out-of-pocket expenses are all ways to quantify healthcare. By comparing these features across countries, we may learn how well those health insurance systems work. The qualitative part of the study looks at how laws and policies that target the coordination of socioeconomic institutions impact the availability and affordability of health insurance. Though AB-PMJAY improved access, it had the opposite effect on administrative efficiency, horizontal equity, and financial sustainability in India, according to the study. India can tweak a few processes by comparing tax-funded, social insurance, and mixed-models. Together, we can accomplish strong leadership, public-private partnerships, and protections for vulnerable communities. Universal health coverage, better health care accessibility and sustainability, and stronger health insurance are all things that the study suggests addressing.